(untitled) (Journal of Partial Differential Equations, 2020)
" We revise one case of theM-solutions of [1, B.Wang, Z. C. Zhang, Y. Li, The radial positive solutions of the Matukuma equation in higher dimensional space: Singular solution, J. Differential Equations 253 (2012), 3232-3265.] and obtain more precise form of the singular term and the regular term."